2023
DOI: 10.3389/fpls.2023.1188627
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure analyses in barley (Hordeum vulgare) against corn-leaf aphid, Rhopalosiphum maidis (Fitch)

Sunny Maanju,
Poonam Jasrotia,
Surender Singh Yadav
et al.

Abstract: Corn-leaf aphid (CLA), Rhopalosiphum maidis (Fitch) (Hemiptera: Aphididae) is a serious economic pest of barley worldwide. Breeding for aphid resistance in plants is considered a cost-effective and environmentally safe approach for aphid control, compared to the use of chemical pesticides. One of the challenges in breeding for aphid resistance is the identification of resistant plant genotypes, which can be achieved through the use of molecular markers. In the present study, a set of aphid specific 10 simple-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…As a molecular marker, SSR is of great significance in plant disease resistance breeding [ 38 , 39 ]. Maanju et al [ 40 ] used a set of aphid specific 10 SSR markers to analyze the genetic diversity and population structure of 109 barley genotypes against R. maidis , and They found that only 2 genotypes were found to be resistant against Corn-leaf aphid (CLA). Sonah et al [ 41 ] established an online database of genome-wide SSR markers called ‘BraMi’ (Brachypodium microsatellite markers), enriching resources for plant genome research.…”
Section: Discussionmentioning
confidence: 99%
“…As a molecular marker, SSR is of great significance in plant disease resistance breeding [ 38 , 39 ]. Maanju et al [ 40 ] used a set of aphid specific 10 SSR markers to analyze the genetic diversity and population structure of 109 barley genotypes against R. maidis , and They found that only 2 genotypes were found to be resistant against Corn-leaf aphid (CLA). Sonah et al [ 41 ] established an online database of genome-wide SSR markers called ‘BraMi’ (Brachypodium microsatellite markers), enriching resources for plant genome research.…”
Section: Discussionmentioning
confidence: 99%